A Comparison of the Effectiveness of Emotional Cognitive Regulation Strategies and Self-Regulated Learning Strategies on Academic Self-Concept and Cognitive Flexibility in Elementary School Students with Specific Learning Disabilities in Reading - Tabari Far, Fatemeh; Ghanadzadegan, Hosseinali; Heydari, Shaban (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to compare the effectiveness of emotional cognitive regulation strategies and self-regulated learning strategies on improving academic self-concept and cognitive flexibility in elementary school students diagnosed with specific learning disabilities in reading. Methods and Materials: A quasi-experimental pre-test, post-test, and follow-up design was used, involving 60 students with specific reading disabilities from elementary schools in Sari, Iran. Participants were randomly assigned to one of three groups: emotional cognitive regulation training, self-regulated learning training, or a control group. Each experimental group consisted of 20 students who underwent 8 sessions of their respective intervention. Data were collected using two standardized questionnaires: the Academic Self-Concept Questionnaire (Chen, 2004) and the Cognitive Flexibility Inventory (Dennis & Vander Wal, 2010). Statistical analysis was performed using multivariate analysis of covariance (MANCOVA) and Bonferroni post-hoc tests.Findings: Both emotional cognitive regulation and self-regulated learning strategies significantly improved academic self-concept and cognitive flexibility compared to the control group (p < .001). No significant differences were found between the two experimental groups in terms of academic self-concept (p = .102) or cognitive flexibility (p = .241). The Bonferroni post-hoc test confirmed that both interventions were equally effective in enhancing the targeted outcomes. Conclusion: The findings indicate that emotional cognitive regulation and self-regulated learning strategies are equally effective in improving academic self-concept and cognitive flexibility in students with specific learning disabilities in reading. Both interventions offer valuable tools for educators to support these students' academic and emotional development.